2022
DOI: 10.1097/j.jcrs.0000000000000821
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods to calculate the axial length measured by optical biometry

Abstract: The optical biometer using group refractive index overestimates AL compared with the device based on segmented AL. Cooke-modified AL is the closest to segmented AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
0
19
0
2
Order By: Relevance
“…They found statistically significant differences between ALs, with a traditional AL shorter in short eyes and longer in long eyes. Savini et al 27 described how also an SS-OCT optical biometer based on the GRI (IOLMaster 700; Carl Zeiss Meditec, AG) overestimates AL compared to the device using segmented AL in long eyes (Argos). The effect of these differences on IOL power calculation were not evaluated in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…They found statistically significant differences between ALs, with a traditional AL shorter in short eyes and longer in long eyes. Savini et al 27 described how also an SS-OCT optical biometer based on the GRI (IOLMaster 700; Carl Zeiss Meditec, AG) overestimates AL compared to the device using segmented AL in long eyes (Argos). The effect of these differences on IOL power calculation were not evaluated in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the medium-long eyes, especially, the predictive accuracy of SS-OCT for IOL calculations was higher than PCI [ 23 ]. However, it is known that the SS-OCT biometer with group refractive index (IOLMaster 700) overestimates AL compared to the device providing segmented AL in the long eyes, and Cooke-modified AL (CMAL) is the adjusting method that gives the AL values closest to the segmented axial length [ 24 ]. In our research, we used the self-control method which compared one patient's preoperative and postoperative data, and thus, we considered that adjusted AL was not a must in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In pseudophakic eyes, optical biometers modify AL calculation according to the corrections recommended by Haigis. 1 These corrections are applied throughout the whole AL range, and for this reason, De Bernardo et al found a similar AL shortening in long, medium, and short eyes. Other authors have also reported almost identical outcomes using sweptsource optical coherence tomography optical biometry.…”
mentioning
confidence: 95%
“…2 The results by Savini et al (AL obtained by Argos vs AL obtained by IOLMaster 700) are similar to those obtained in the paper by De Bernardo et al because a similar AL difference (−0.10 mm) was found between preoperative AL measurements with the phakic option vs postoperative AL with the pseudophakic option, both obtained by IOLMaster 500. 1 The reason why we wrote in part is because in the paper by De Bernardo et al, the AL shortening was obtained not only in long but also in short and normal eyes. 2 For this reason, we wonder whether the AL shortening after cataract surgery could be related not only to the group refractive index, but other reasons could be involved.…”
mentioning
confidence: 96%